(untitled) (European Bison Conservation Newsletter, 2010)
In the second half of the XXth century, 6 subpopulations of European bison were created in the western part of Ukraine: three in the mountains and three at the plains. In the 70ties of the XXth century, Klevan subpopulation ceased to exist, at the beginning of the XXIth century Tsuman and Skole subpopulations were on the verge of disappearance, and E. bison numbers in Bukovyna became strongly reduced. A study on the influence of environmental factors upon the bison numbers in the western part of Ukraine was held between 1999 and 2010. In that period, 131 cases of bison death were registered. Seven major causes of bison death have been identified: food shortage, poaching, diseases, accidents, ageing, predation. The main factors which caused reduction of E. bison population numbers were poaching and diseases, and in the mountain conditions this was also a shortage of forage. In many cases it turned out to be impossible to determine the cause of animals’ death.